Case Report: Successful Treatment of Solitary Fibrous Tumor with Selective Internal Radiation Therapy (SIRT) - Omar Badran; Sergey Dereza; Labib Mireb; Ziv Neeman; Gil Bar-Sela (Diseases)
Background: This case report details the innovative use of selective internal radiation therapy (SIRT) with Yttrium-90 resin microspheres to treat a 73-year-old woman with a solitary fibrous tumor (SFT), a rare and challenging tumor type. SFTs often present significant treatment difficulties, especially in cases of recurrence or metastasis, as systemic therapies typically show limited effectiveness. This report explores SIRT as an alternative therapeutic approach for SFTs with liver metastasis. Methods: The patient initially presented with a pelvic mass, which was surgically resected. However, metastatic disease later developed in the liver. After experiencing severe side effects from targeted therapy with sunitinib, the patient was selected for treatment with SIRT as an alternative. Results: Following the SIRT intervention, the patient demonstrated a substantial reduction in tumor size and significant relief from symptoms. This outcome suggests SIRT’s effectiveness as a targeted treatment for metastatic SFT. Conclusions: To our knowledge, and based on an extensive literature review, this is the first reported instance of treating SFT with SIRT. This case provides new insights into SIRT’s potential as a therapeutic strategy, particularly for patients for whom conventional treatments are either ineffective or intolerable. The success observed here underscores SIRT’s potential as a less invasive, locally targeted treatment option, offering hope for similar cases.